α-Mangostin Exhibits Antitumor Activity Against NCI-H1975 Cells via the EGFR/STAT3 Pathway: An Experimental and Molecular Simulation Study - Jing Wang; Jiamin Xian; Ruohan Zhang; Zhuoyi Wang; Shuanggou Zhang; Die Zhao; Jun Sheng; Peiyuan Sun (Molecules)
Non-small cell lung cancer (NSCLC) harboring epidermal growth factor receptor (EGFR) mutations have brought great challenges to the medical treatment in the world. Current treatment strategies, such as EGFR tyrosine kinase inhibitors (TKIs), have reached certain achievements, however, patients inevitably experienced resistance after undergoing a period of treatment with these drugs. Hence, more novel therapy strategies need to be urgently developed. Natural compounds have become popular topics in drug development. α-Mangostin, which is derived from mangosteen, possesses multiple biological properties, yet the antitumor mechanism against NSCLC has not been further elucidated. In this study, an MTT assay, Western blotting, a colony formation assay, and flow cytometry were performed to detect the antitumor activity of α-Mangostin on NSCLC cell NCI-H1975. Molecular docking and molecular dynamics simulations were performed to analyze the interactions between α-Mangostin and the core target proteins. The results indicated that α-Mangostin exerts its antitumor activity by inhibiting cell proliferation and migration, reducing cell cycle arrest, promoting cell apoptosis, and regulating the phosphorylation expression levels of EGFR and signal transducer and activator of transcription 3 (STAT3). Moreover, the results of the molecular simulation study revealed the potential binding mode of α-Mangostin to EGFR and STAT3. In summary, we characterized that α-Mangostin may be used as a potent pro-drug against NSCLC via the EGFR/STAT3 pathway.